The correlation between Overweight and Age at Menarche Students at Pangudi Luhur Bintang Laut Junior High School Surakarta - Rina Dwi Purnamasari; Yulia Lanti Retno Dewi; Rosalia Sri Hidayanti (Nexus Kedokteran Komunitas, 2014)
Backgrounds: Age at menarche has declined in many countries. Decline in age at menarche is correlated with increase risk factor of many diseases. Overweight is known as one of many factors that affect menarche age. This research aim to determine the correlation between overweight and age at menarche in students at Pangudi Luhur Bintang Laut Junior High School Surakarta. Methods: This research used observational analytical study with the cross sectional approach. The subject of the research were female students of 7th grade at Pangudi Luhur Bintang Laut Junior High School in Surakarta that taken by purposive and simple random sampling techniques. 155 female students had to fill questionnaire about age at menarche. Weight and height of 155 female students were measured to calculate BMI. The final result of restricted samples were 30 female students classified as overweight. The collected data were analyzed with Spearman correlation test. Results: The result of Spearman correlation test was 0.277 as p value. So, there wasnt a significant correlation between variables. Conclusions: This study shows no relationship between overweight and age at menarche students at Pangudi Luhur Bintang Laut Junior Hight School Surakarta. Keywords: overweight; age at menarche